2007
DOI: 10.1002/zaac.200700302
|View full text |Cite
|
Sign up to set email alerts
|

Inkommensurabel modulierte Kristallstrukturen und Phasenumwandlungen – Die Verbindungen SrPt2As2 und EuPt2As2

Abstract: The new compounds SrPt 2 As 2 (a ϭ 4.482(1), b ϭ 4.525(1), c ϭ 9.869(2) Å ) and EuPt 2 As 2 (a ϭ 4.435(2), b ϭ 4.467(2), c ϭ 9.784(3) Å ) have been prepared by reaction of the elements at 1050°C. Satellite reflections observed in X-ray diffraction experiments on single crystals revealed that both compounds have modulated crystal structures at room temperature. The average structures can be derived from the CaBe 2 Ge 2 type and described in the orthorhombic space group Pmmn (Z ϭ 2) with splitted positions for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
65
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 21 publications
13
65
2
1
Order By: Relevance
“…23) In accordance with this prediction, SrPt 2 As 2 exhibits a CDW transition at about 470 K. Imre et al reported that a structural modulation develops with a modulation vector of q ¼ 0:62a à in the -As-Pt-As-layers with PtAs 4 tetrahedra below about 470 K, whereas the -Pt-As-Pt-layers with Pt 4 As tetrahedra remain intact. This modulation leads to a structural distortion from the high-temperature tetragonal phase with the CaBe 2 Ge 2 -type structure to the low-temperature CDW phase with the average structure of the orthorhombic space group Pmmn (#59).…”
supporting
confidence: 53%
See 2 more Smart Citations
“…23) In accordance with this prediction, SrPt 2 As 2 exhibits a CDW transition at about 470 K. Imre et al reported that a structural modulation develops with a modulation vector of q ¼ 0:62a à in the -As-Pt-As-layers with PtAs 4 tetrahedra below about 470 K, whereas the -Pt-As-Pt-layers with Pt 4 As tetrahedra remain intact. This modulation leads to a structural distortion from the high-temperature tetragonal phase with the CaBe 2 Ge 2 -type structure to the low-temperature CDW phase with the average structure of the orthorhombic space group Pmmn (#59).…”
supporting
confidence: 53%
“…SrPt 2 As 2 crystallizes in a tetragonal CaBe 2 Ge 2 -type structure with the space group P4=nmm (#129), 23) as shown in Fig. 1(a).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…We considered the fact that a second transition metal should be one that can adopt coordination geometries other than tetrahedral. Platinum appeared promising, because Pt is known to be very flexible and forms arsenides with octahedral, tetrahedral, trigonal and square coordination in compounds like PtAs 2 , [10] SrPt 2 As 2 , [11] SrPtAs, [12] and Cs 2 PtAs 2 , [13] respectively. Recently, Nohara et al [14] mentioned superconductivity in the system Ca-Fe-Pt-As, but the structure and composition of the compound have not been reported.…”
Section: Catrin Löhnert Tobias Stürzer Marcus Tegel Rainer Frankovmentioning
confidence: 99%
“…When it comes to the iridium arsenides, only the phases REIr 2 As 2 (RE = La -Nd [21], K, Rb [11], Cs [10], Sr [23]), Mg 4 Ir 7 As 6 [24], and Ca 4 Ir 8 As 7 [13] are known. In continuation of our work on rare earth metal-iridium-phosphides, we tested the leadflux technique also for the arsenides.…”
Section: Introductionmentioning
confidence: 99%